Calculate y'' and y'''.
We can use the product rule to find the first derivative, y', since function y is the product of two functions, θ2 and 4·θ + 5. However, expanding their product first will simplify the process for finding the higher derivatives of y.
y = θ2(4·θ+5)
= 4·θ3 +·θ2
In order to calculate the second derivative, y'', we need to calculate first y'.
y = 4·θ3 + 5·θ2
y' = ·θ2+·θ
Now, calculate y'' by taking the derivative of y'.
y' = 12·θ2 + 10·θ
y'' = ·θ +
Finally, calculate y''' by taking the derivative of y''.
y'' = 24·θ + 10
y''' =